Leukocyte Telomere Length Shortening Implies Plaque Instability and Major Adverse Cardiovascular Events in Patients With Angiographically Intermediate Lesions - Zhang, Alian; Fan, Li; Bao, Xiaolu; Xu, Zuojun; Yin, Zhaofang; Zhuo, Yang; Zhang, Junfeng; Gu, Jun; Chang, Alex C. Y.; Fan, Yuqi; Wang, Changqian (Frontiers in Cardiovascular Medicine, 2022)
Background: Telomere shortening, an indicator of aging, is associated with age-related diseases. This study aims to investigate the association between leukocyte telomere length (LTL) and thin-capped fibroatheromata (TCFA), and the impact of using LTL cutoff to determine the incidence of major adverse cardiovascular events (MACE) in patients with angiographically intermediate coronary lesions. Methods: This was a signal-center retrospective study focusing on patients whom underwent coronary angiography and optical coherence tomography (OCT). Degree of coronary stenosis was assessed by angiography. Presence of TCFA was determined by OCT imaging. A total of 156 patients with angiographically intermediate coronary lesions were enrolled. Results: LTLs were significantly shorter in the TCFA group compared to non-TCFA group [11.95 (10.56, 15.21) kb vs.13.81 (12.06, 16.11) kb, p = 0.003]. Short-LTL group and long-LTL group were divided according to the optimal cut-off value which determined by the ROC curve analysis. Logistic regression model revealed that short-LTL was independently associated with TCFA incidence (OR 4.387, 95% CI: 1.902-10.120, p = 0.001) after adjusting for confounding factors. Over a 24-months follow-up, the MACE incidence among short-LTL patients was significantly higher than those in the long-LTL group (12.5% vs 2.0%, p = 0.006 by log-rank test). Multivariable cox regression analysis indicated that short-LTL (HR 9.716, 95% CI: 1.995-47.319, p = 0.005) was an independent prognostic factor of MACE incidence in angiographically intermediate coronary lesions patients. Conclusions: Short-LTL was independently associated with the incidence of TCFA and may serve as a prognostic factor for MACE risk on top of conventional risk factors.